Politeness Strategy Used by Ellen DeGeneres in Interviewing Children and Adults on The Ellen Show - Nasir, Al Jumrah; Taufik, Muhammad; Dahniar, Dahniar (English Literature Studi Program Universitas Islam Makassar, 2023)
This research discusses the politeness strategies used by Ellen DeGeneres in interviewing children and adults on The Ellen Show. This research uses a descriptive qualitative method. This research aims to describe the politeness strategies and the differences in politeness strategies addressed by Ellen when interviewing children and adults. The theory applied to explain the analysis of politeness strategies is Brown and Levinson's theory (1987). The results showed that Ellen's talk show host delivered four politeness strategies with different breakdowns. The politeness strategy that tended to be used for children is the positive politeness strategy at (62,5%). The other most used are negative politeness (18,8%), off-record strategies with (12,2%), and bald of record (6,3%). Meanwhile, for adults, Ellen dominantly reckoned to Positive Politeness strategies (72,2%), followed by negative politeness (16,7%), bald of record, and Off Record strategies (5,6%). Positive politeness is the most common form used by Ellen in interviewing her guests, however, there were differences between the two. The differences between children and adults are there several points that researcher found one of them, the use of politeness that is not found in adults but used by children, namely the politeness of apologies, having an unconfident attitude, and avoiding conflict mean that Ellen applies this politeness so that children feel comfortable when talking and can familiarize themselves with children. In addition, this is also a form of attention and teaches children to know where they are wrong.